Thermal Stress Analysis of Dual Active Bridge DC-DC Converter Under Battery Pulsed Current Charging Strategy - Akboy, Erdem; Tahir, Muhammad Usman; Sangwongwanich, Ariya; Stroe, Daniel Ioan; Blaabjerg, Frede (IEEE, 2024)
The pulse current (PC) charging strategy is considered an effective charging strategy to prolong the lifetime of lithium-ion batteries (LIBs). However, the impact of pulsing current on the load dynamics of power converters and its resulting thermal stress in electric vehicles (EVs) has not been investigated in previous studies. This is an important aspect that strongly affects the reliability and lifetime of power converters. Therefore, in this paper, thermal stress analysis of dual active bridge (DAB) converter-based EV chargers with PC strategy is conducted under various parameter conditions, e.g., pulse frequencies and cooling conditions. In addition, the effects of PC frequencies on thermal cycling are evaluated under square wave current reference for the frequency range from 0.05 Hz to 1 Hz. According to the results, the thermal stress (e.g., thermal cycling) of the DAB converter is significant when a low-frequency PC is applied. Furthermore, the performance of the liquid cool system is good compared to the air cool system. Therefore, this research can support the charge point operators (COP) in optimizing the charging system according to the application requirements.
Keywords: Charging Strategy; Dual Active Bridge Converter; Pulse Current Charging; Thermal Analysis; Electric Vehicle; Energy & Fuels; Engineering